Otonomi Desa Dan Efektifitas Efisiensi Tata Kelola Dana Desa di Kabupaten Sidoarjo - Pradita, Fajar (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
Financial management is included in the village's autonomous rights. The current program given by the government is the provision of village funds. Providingvillage fund programs to finance implementation of development, and empoweringvillage communities. The results of the analysis show that village financial managementin Sidoarjo Regency is in accordance with the provisions stipulated by the centralgovernment referring to Regulation of the Minister of Home Affairs number 113 of2014, where in the budgeting process through funding procedures, the implementationof fund disbursement, administration, accountability reporting and publication . Indetermining the priority of the use of funds in accordance with the provisions of theVillage Minister Regulation Number 21 of 2015 and guided by the Village RKP andRPJM, where in the preparation of the Village RKP and RPJM involves all elements ofgovernment, BPD and the community in general. The constraints faced are the problemof using village funds for activities that do not appear in the account code of thesiskeudes, as well as getting around the priority of village development activities thatcome out of the Minister of Home Affairs Regulation number 113 of 2014. Keyword: village autonomy, efficiency effectiveness, village funds